2015
DOI: 10.1016/j.jtcvs.2014.11.032
|View full text |Cite
|
Sign up to set email alerts
|

A time-related parametric risk factor analysis for postoperative atrial fibrillation after heart surgery

Abstract: Phase I and phase II periods are associated with distinct risk factors; therefore, it is likely that the mechanisms of postoperative atrial fibrillation change over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 25 publications
3
58
1
4
Order By: Relevance
“…3 Melby et al reported that patients receiving MVS had a higher risk of POAF compared with patients receiving CABG. 12 The present study showed that the incidence of postoperative heart failure tended to be higher in patients with POAF, and 2 patients had cerebral infarction during POAF. Furthermore, in patients with degenerative disease, the presence of POAF significantly prolonged hospital stay by more than 27 days.…”
Section: Discussionsupporting
confidence: 50%
“…3 Melby et al reported that patients receiving MVS had a higher risk of POAF compared with patients receiving CABG. 12 The present study showed that the incidence of postoperative heart failure tended to be higher in patients with POAF, and 2 patients had cerebral infarction during POAF. Furthermore, in patients with degenerative disease, the presence of POAF significantly prolonged hospital stay by more than 27 days.…”
Section: Discussionsupporting
confidence: 50%
“…POAF typically occurs on postoperative day 2, with 70% of cases occurring within the first four postoperative days [32]. Melby et al [33] conducted a time series analysis on patients after bypass and valvular surgeries and documented two postoperative periods where patients are at highest risk of POAF. They proposed a trajectory whereby the highest risk occurs immediately after surgery with a second increase in risk occurring 48 h postoperatively.…”
Section: Postoperative Atrial Fibrillation After Cardiac Surgerymentioning
confidence: 99%
“…Recently, incidence rates of new-onset POAF after isolated aortic valve replacement (AVR) or CABG with concomitant AVR were 28% and 39%, respectively. 4 New-onset POAF appeared to affect both mental and physical health months after CABG. 5 In some studies, new-onset POAF was associated with decreased 30-day survival after cardiac surgery.…”
mentioning
confidence: 99%